A worldwide survey of the reporting of human rabies - Taylor, L. H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Without accurate reporting of human rabies cases, it is impossible to assess the true burden of the disease on countries, to assess how much resources a government should allocate to rabies control, or to carry out cost-benefit analyses on rabies prevention efforts. The Global Alliance for Rabies Control (GARC) with the Partners for Rabies Prevention is conducting a global survey of human rabies reporting practices. We want to gain a global picture of where human rabies is a notifiable disease and to assess whether the systems in place for the reporting of cases are perceived to be adequate. Networks of rabies experts have been asked to complete a short survey which collected information on whether human rabies was notifiable, which authorities were responsible for the collation and reporting of cases, whether the system was effective, and some details of what data is collected and how it is disseminated. The survey is available online in a user-friendly format in English, French or Spanish. Preliminary results from 104 respondents in 69 countries have been analyzed and show that human rabies is a notifiable disease in 61 (88%) of these countries. However, respondents indicated that the reporting system was ineffective for 23% of the countries where rabies was notifiable. A regional analysis suggests that the countries where rabies is not notifiable, or where the system is ineffective are almost all in Africa and Asia where the burden of human rabies is highest, and more investment in rabies control is badly needed.